The Impact of ARKAS Implementation on BOS Fund Reporting in Elementary Schools in Sanggau Regency - Muhammad Anshari; Nella Yantiana; Haryono Haryono; Rusliyawati Rusliyawati; Juanda Astarani (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the effect of the implementation of the School Activity and Budget Plan Application (ARKAS) on the reporting of School Operational Assistance (BOS) funds in elementary schools in Sanggau Regency. The research method employed is quantitative, using a Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS). The sample consists of principals and treasurers from 142 elementary schools that have used ARKAS for at least one year. Data was collected through questionnaires and analyzed using SmartPLS software. The results indicate that the implementation of ARKAS has a positive and significant effect on BOS fund reporting. These findings underscore the importance of optimizing the use of ARKAS, as well as the active roles of school leaders and treasurers in improving the accuracy, timeliness, and compliance of BOS fund reporting.